Role of calcium signaling in the transcriptional regulation of the apicoplast genome of Plasmodium falciparum - Cheemadan, Sabna (2014)
Calcium is a universal second messenger that plays an important role in regulatory processes in eukaryotic cells. To understand calcium-dependent signaling in malaria parasites, we analyzed transcriptional responses of Plasmodium falciparum to two calcium ionophores (A23187 and ionomycin) that cause redistribution of intracellular calcium within the cytoplasm. While ionomycin induced a specific transcriptional response defined by up- or downregulation of a narrow set of genes, A23187 caused a developmental arrest in the schizont stage. In addition, we observed a dramatic decrease of mRNA levels of the transcripts encoded by the apicoplast genome during the exposure of P. falciparum to both calcium ionophores. Neither of the ionophores caused any disruptions to the DNA replication or the overall apicoplast morphology. This suggests that the mRNA downregulation reflects direct inhibition of the apicoplast gene transcription. Next, we identify a nuclear encoded protein with a calcium binding domain (EF-hand) that is localized to the apicoplast. Overexpression of this protein (termed PfACBP1) in P. falciparum cells mediates an increased resistance to the ionophores which suggests its role in calcium-dependent signaling within the apicoplast. Our data indicate that the P. falciparum apicoplast requires calcium-dependent signaling that involves a novel protein PfACBP1.